2007
DOI: 10.1002/ijc.22925
|View full text |Cite
|
Sign up to set email alerts
|

Total loss of HLA class I expression on a melanoma cell line after growth in nude mice in absence of autologous antitumor immune response

Abstract: Loss of HLA class I expression on tumor cells is a frequent event as an immune escape mechanism. Seven different altered HLA phenotypes have been defined in tumors. Various molecular mechanisms have been described as responsible for HLA class I loss. HLA class I expression alterations occur successively and unpredictably during tumor progression in vivo and immunoselection has been implicated in this process. We present an experimental xenograft model in which melanoma cell line Ando-2 injected into athymic nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…On the other hand, trichostatin A counteracted HLA down-modulation in IGROV-1 cells, a finding suggesting that histone acetylation may represent an additional relevant mechanism, as previously reported in a different setting [3]. These data are also in line with a previous study reporting an epigenetic effect of the microenvironment, where bystander stromal cells may have a major influence on the growth and progression of tumors [14].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, trichostatin A counteracted HLA down-modulation in IGROV-1 cells, a finding suggesting that histone acetylation may represent an additional relevant mechanism, as previously reported in a different setting [3]. These data are also in line with a previous study reporting an epigenetic effect of the microenvironment, where bystander stromal cells may have a major influence on the growth and progression of tumors [14].…”
Section: Discussionsupporting
confidence: 88%
“…To evaluate this possibility, we cultured tumor cells explanted ex vivo with different epigenetic drugs (namely, trichostatin A and decitabine) that had already proven to be effective in vitro [3, 4] or in vivo [1], respectively. Surprisingly, we observed that the simple placement of tumor cells in complete medium, without the addition of any drug, led to reversion of the down-modulated phenotype (when present) within a few hours (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed both vectors carrying HLA-A2 gene and compared their efficacy to induce HLA-A2 transgene expression in different tumor cell lines. Using these viral vectors, we successfully recovered HLA-A2 expression in melanoma cell line Ando-2 which has been characterized to lack endogenous HLA-A2 due to a haplotype loss caused by loss of heterozygosity at chromosome 6 (Table 1) [26]. (Table 1).…”
Section: Comparative Analysis Of the Transduction Efficacy Of Adenovimentioning
confidence: 99%
“…All melanoma cell lines, except for Ando-2, were obtained from the European Searchable Tumour Cell Line Data Base (ESTDAB) [24] and have been previously genotyped for HLA-I and characterized for HLA phenotype [25]. Ando-2 was kindly provided by Dr P. Coulie (Université Catholique de Louvain (UCL), Brussels, Belgium) and is characterized by the loss of HLA-A2 expression due to HLA-I haplotype loss [26]. Prostate cancer cell lines DU145 and PC3, as well as bladder cancer cell lines T24, WIL and RT112, were obtained from American Type Culture Collection (ATCC).…”
Section: Cell Linesmentioning
confidence: 99%